Analisis Gangguan Bahasa Pada Anak Melalui Kajian Psikolinguistik - Rifki Yoga Pratama (FASHOHAH, 2022)
This analysis focuses on interdisciplinary psycholinguistics regarding language disorders in children. This article analyzes two children with language disorders. Language disorders in children often occur due to problems such as what will be discussed about what factors affect children's language disorders, knowing the indicators of language disorders in children. This analysis is intended for children aged over 3 years who have language disorders as well as the research we have done on children aged 9 years and over 6 years who have speech delays in children, the factors that influence and how speech delays occur in children. . The research method used is descriptive qualitative research method. The method aims to describe in a systematic, actual, and accurate way. This research is a research analysis of official documents such as books, articles, journals, and the internet. The accuracy of the data is obtained from the observations of the researchers themselves. The research instrument is the human instrument. Researchers become the main data collection tool as well as directly analyze the data